2017
DOI: 10.1093/jncics/pkx009
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Early Mortality in Colorectal Cancer Patients Undergoing Chemotherapy: Results From a Global Prospective Cohort Study

Abstract: Background Early mortality is a major problem in colorectal cancer (CRC). We have shown that Khorana Score is predictive of early mortality in other cancers. Here, we evaluated the value of this score and other prognostic variables in predicting early mortality in CRC. Methods CANTARISK was a prospective, noninterventional, global cohort study in patients with CRC initiating a new chemotherapy regimen. Data were collected at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…The findings pointed to the presence of an independent predictive relationship between baseline KRS before chemotherapy and death within 2 years in patients with GC and CRC. This result is comparable to a global prospective study by Sohal et al [ 7 ], which observed that KRS predicted mortality within 6 mo in patients with CRC treated using chemotherapy. Moreover, similar findings have been reported for different tumor types in studies by Shibata et al [ 10 ], Kuderer et al [ 11 ], Mansfield et al [ 12 ], and Vathiotis et al [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings pointed to the presence of an independent predictive relationship between baseline KRS before chemotherapy and death within 2 years in patients with GC and CRC. This result is comparable to a global prospective study by Sohal et al [ 7 ], which observed that KRS predicted mortality within 6 mo in patients with CRC treated using chemotherapy. Moreover, similar findings have been reported for different tumor types in studies by Shibata et al [ 10 ], Kuderer et al [ 11 ], Mansfield et al [ 12 ], and Vathiotis et al [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, a 2018 systematic review observed that the score exhibited poor predictive power for individual tumor types, and unexpectedly, higher scores were associated with a higher risk of early death[ 5 ]. Some prospective studies have demonstrated its ability to predict early death in lung and colorectal cancers[ 6 , 7 ]. However, studies on the relationship between KRS and all-cause mortality are limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, both all-cause and VTE-related healthcare costs significantly increased with KS. All-cause healthcare costs were predominantly driven by non-VTE-related costs across all KS cohorts in the current study, which aligns with previous studies that have found KS to be predictive of early mortality and cancer progression during the first four cycles of outpatient chemotherapy, independent from other major prognostic factors including VTE itself [32][33][34].…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Patients with cancer at high risk of VTE may incur higher healthcare costs than those at lower risk due to increased risk of early mortality and cancer progression [32][33][34], along with greater burden of VTE-related expenses and ensuing complications, including VTE recurrences, postthrombotic syndrome, and pulmonary hypertension [35]. However, among studies that assessed the economic burden of cancer-associated VTE, none stratified patients into different VTE risk cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, there was 1.6 millions incidents of colorectal cancer and 771 000 deaths. 8 Moreover, the incident number shows a significant rise. Surgery with combination of adjuvant radiochemotherapy are the main treatment of colorectal cancer.…”
Section: Figure 1: Immunostaining Of Ki67 40% A) 60% B) 70% C) 80mentioning
confidence: 99%